3x-9=27...Add 9 to each side of the equation and therefore, that will
leave you with 3x=36. Then, divide 3 to each side of this equation
and that will leave you with X=12(answer). Replace x with the number 12 and you
will have 3(12)-9=27...36-9=27.
Do the same with 2x+4=44. Subtract 4 from each side of the equation and
therefore, you will have 2x=40. Then divide 2 to each side of this equation
which will leave you with x=20(answer). Replace x with the number 20 and you
will have 2(20)+4=44. Thus, 40+4=44.
4(7x-9)+6=82...Remember P.E.M.D.A.S, Multiply 4 by 7x, this equals 28x. Then multiply 4 by -9=-36. Now, you have 28x-36+6=82. Combine like terms. Which is -36+6=-30. So, 28x-30=82. Add 30 to both sides of the equation. This leaves you with 28x=112. Divide 28 to both sides. X=4(answer). Thus, replace 4 with x.